Towards a Model to Explore Business Opportunities in Trail-aware Environments - Martins, Cládio; Rosa, João; Barbosa, Jorge; Franco, Laerte; Bezerra, Eduardo (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2012)
In mobile computing environments, the tracking of users allows applications to adapt to the users’ contexts (Context Awareness). Context, in this sense, is any information that can be used to characterize the users’ situations and that is relevant to the interaction between the user and an application. In recent years, the use of context information and users’ profiles have been considered an opportunity for ubiquitous commerce. Furthermore, the improvement and the wide adoption of location systems are stimulating the tracking of users, allowing the use of trails. A trail is the history of the contexts visited by a user during a certain period. In this article, we propose a model for trails management and its application in ubiquitous commerce. In this text, we consider that Trail Awareness is an advance of the simple use of contexts and profiles. We present a prototype and its application in a simulated commercial environment for discovery of deal opportunities using trail awareness.